Current-step technique to enhance plasma focus compression and neutron yield - Lee, S.; Saw, S. H. (Springer US, 2012)
A current-step technique is applied to the plasma focus by modifying the Lee Model code, incorpo- rating a current-step bank to add current to the focus pinch at the time of the current dip. For a 50 kV, 1 MJ, 6 ls rise- time bank, the current-step from a 200 kV, 0.4 MJ, 0.8 ls rise-time bank maintains the pinch current at 2.2 MA, enhances compression by 1.9 and increases the neutron yield from 2.5 9 10 12 to 1.03 9 10 13 . The increase is attributed mainly to the step nature of the current which favorably shifts the end-point of compression; rather than to the scaling in terms of energy or current.